ANALISIS KEPUASAN KONSUMEN KOPI JANJI JIWA JILID 57 DI KOTA MANADO (Consumer Satisfaction Analysis of â€œKopi Janji Jiwa Jilid 57â€ in Manado City) - Sitinur Fahriani Ali; Juliana R. Mandei; Grace A. J. Rumagit (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2020)
The objective of this research is to analyze the consumer satisfaction of â€œKopi Janji Jiwa Jilid 57â€ in Manado City. This research was conducted for 4 months, starting from November 2019 to February 2020. The data used are primary data and secondary data. Primary data is data obtained from direct interviews with 70 respondents using questionnaires, while secondary data is obtained from business owners, the internet and other sources relevant to this study.The research result showed that the consumer satisfaction of â€œKopi Janji Jiwa Jilid 57â€ on Jalan August 17 in Manado through product, price, place, promotion and service quality variables, reached a total score of 6,045 indicating a consumer satisfaction index of 78.50% and classified as on satisfied criteria. Product is the variable with the highest level of satisfaction which is 85.64% and can be classified as very satisfied. The other four variables are classified as satisfied, which are promotion (78.10%), service quality (77.89%), price (77.83%), and place (74.34%). This result showed that consumers are generally satisfied with all variables of â€œKopi Janji Jiwa Jilid 57â€Keywords: Kopi Janji Jiwa, Consumer satisfaction